The Development of Smart Snake and Ladder Media in Mastery of English Vocabulary Grade III at SDI Babussalam Pandean Durenan Trenggalek - Uswatun Kasanah; Muhamad Zaini; Nur Efendi; Adi Wijayanto; Eni Setyowati (CV. Tripe Konsultan, 2022)
The monotonous learning media in English vocabulary, and memorizing method make students bored, so needed media innovations for these lessons, such as Smart Snake and Ladder. This paper aims to develop learning media Smart Snake and Ladder in mastering English vocabulary. The type of research used is R&D. The results of this research and development, showed that: (1) The development of the Smart Snake and Ladder media product pays attention to the safe appearance, and modified ways of playing to attract the user's attention, curiosity, and describe the theme material for elementary school children. (2) The development of smart snake and ladder media is very valid and feasible to use to improve English vocabulary mastery, as the validation results from material experts I get a 100% validity level and material II experts get 92.5%, media experts I 81.25 %, media experts II 85%, and media experts III 84.37%. (3). The effectiveness of using smart snake and ladder media can be seen from the pre-test and post-test data. The average value of the pre-test is 81.87 while the average value of the post-test is 96.20. Apart from the pre-test and post-test data, it can also be seen from the student assessment data with an average score of 99.9%.